Analysis of expression of transcription factors in early human retina. Issue 60 (3rd April 2017) - Chen, Jing; Ma, Lixiang; Wang, Songtao; Wang, Xiaobing; Sun, Yan; Gao, Lu; Li, Jin; Zhou, Guomin
Abstract: The retina originates in the central nervous system. Due to its accessibility and simplicity, the retina has become an invaluable model for studying the basic mechanisms involved in development. To date, considerable knowledge regarding the interactions among genes that coordinate retinal development has been gained from extensive research in model animals. However, our understanding of retinal development in humans remains undeveloped. Here, we analyze the expression of transcription factors that are involved in the early development of the retina in human embryos at 6–12 weeks post‐conception. Our work demonstrates that early developing neural retinas can be divided into two layers, the outer and inner neuroblast layers. Eye‐field transcription factors and those related to the early development of the retina have distinct expression patterns in the two layers. Cell‐type‐specific transcription factors emerge at 8 weeks. These data provide clear and systemic structures for early retinal development in human.